Progress on innate immune evasion and live attenuated vaccine of pseudorabies virus - Nie, Zhenyu; Zhu, Shunfan; Wu, Li; Sun, Ruolin; Shu, Jianhong; He, Yulong; Feng, Huapeng (Frontiers in Microbiology, 2023)
Pseudorabies virus (PRV) is a highly infectious disease that can infect most mammals, with pigs as the only natural host, has caused considerable economic losses to the pig husbandry of the world. Innate immunity is the first defense line of the host against the attack of pathogens and is essential for the proper establishment of adaptive immunity. The host uses the innate immune response to against the invasion of PRV; however PRV makes use of various strategies to inhibit the innate immunity to promote the virus replication. Currently, live attenuated vaccine is used to prevent pig from infection with the PRV worldwide, such as Bartha K61. However, a growing number of data indicates that these vaccines do not provide complete protection against new PRV variants that have emerged since late 2011. Here we summarized the interactions between PRV and host innate immunity and the current status of live attenuated PRV vaccines to promote the development of novel and more effective PRV vaccines.